La pragmática y la hermenéutica como enfoques contemporáneos para una interpretación, práctica y experiencia de los derechos humanos (2021)
This article is an attempt to approach hermeneutically and pragmatically those difficulties presented by human rights in their exercise and implementation by the individual and collective human being in violent countries as Colombia, but also that hope permeates the global sense of the Relationship between State and Human Rights. This phenomenon of inconsistencies between the general postulates and the broad function of the State with the reality of the exercise of Human Rights will be the object of the present to reflect about possible ways of understanding the phenomena associated with Human Rights and to exercise them in an integral way.